Social Media and Brand Personification for Micro and Small Culinary Enterprises: Media Sosial dan Personifikasi Merek untuk Usaha Kuliner Mikro dan Kecil - Tambunan, Leo Alexander; Fanggidae, Paulus Yulius; Suparto, Jessica Dorothy; Sumardin, Peter Frederick; Tejakusuma, Enrico Julio (Indonesian Journal of Innovation Studies, 2026)
General Background: The rapid growth of culinary MSMEs in South Tangerang underscores their strategic role in strengthening regional and national economic resilience. Specific Background: Digital transformation, particularly through social media, has become a crucial tool for MSMEs to enhance visibility and build emotional engagement with consumers. Knowledge Gap: However, empirical studies examining how social media facilitates brand personification and its contribution to MSME business performance remain limited, especially in the culinary sector. Aims: This study aims to analyze the effectiveness of social media in supporting brand personification and its impact on the business development of culinary MSMEs in South Tangerang. Results: Using a qualitative approach with structured interviews, the findings reveal that platforms such as WhatsApp, TikTok, and Instagram significantly strengthen brand identity, foster customer interaction, and enhance consumer trust. Brand personification—expressed through personalized narratives, humanized brand identities, and consistent visual representation—plays a key role in increasing customer engagement and market reach. Novelty: This research offers a practical framework demonstrating how humanized digital branding strategies can be optimized by micro and small culinary entrepreneurs. Implications: The study highlights that effective social media utilization combined with strong brand personification can substantially improve business performance and support MSME growth in competitive digital markets. Highlights: Highlights the strategic role of social media in strengthening brand identity for culinary MSMEs. Emphasizes brand personification as a key factor in building emotional engagement with consumers. Shows that digital branding practices significantly enhance business growth and market reach. Keywords: MSME, Social Media, Brand Personification, Digital Marketing, Culinary Business